Kuat Karakteristik Beton Pracetak Yang Menggunakan Perekat Sebagai Alat Sambung - Delarue, Jeffrey A. (Peneliti.net, 2024)
The use of concrete technology, in particular precast concrete, has been in recently. In recurring and massive work, precast concrete is much more profitable compared with conventional concrete in terms of time, cost and quality of work. One of the factors heeded in precast concrete technology is the connector between precast elements. In general, the connector uses anchors of steel, bolts, and welding. Connector failures are often in the form of the loss of the steel anchor, the disconnection of the reinforced steel and the crack of wet connector using concrete mortar. In line with the development of adhesive industry in Indonesia, this research tried to use adhesive as connector device in precast concrete. It aimed at finding out a comparison between the press force of connected concrete and that of solid concrete, their pull force comparison (splitting and flexibility test) and the influence of concrete age on concrete connecting. The research method used was experimental. The adhesive used was Nitobond EC with connection at 1, 3, 7, 14 and 28 days. As a standard of comparison, concrete was made without adhesive. Test was carried out when the concrete was 28 days old to find out the press force and the pull force (splitting and flexibility test). The research findings indicated that: 1) the material used met the requirements for ASTM C 33. 2) The planned concrete press force 30 MPa was achieved at 28 days of concrete connection age. 3) Results of press and pull test (flexibility test) showed instability of force value at 1 and 3 days concrete age connection, so that the use of this research is at concrete age connection 7, 14 and 28 days. 4) At the concrete age of 7, 14 and 28 days, the press force and full force (splitting and flexibility test) indicated stability of force value and a tendency of increasing force. The press force values were 28.36, 29.87 and 30.29 MPa, respectively. The splitting pull force values were 1.34, 2.12 and 2.2 MPa, respectively. The flexibility pull force values were 4.15, 4.18 and 4.94 MPa. 5) Comparison with solid concrete at maximum value showed: connected concrete pressure force decreased 1.368 % or 0.42 MPa, connected concrete splitting pull force decreased 24. 138 % or 0.7 MPa and connected concrete flexibility pull force increased 1.856 % or 0.09 MPa. Based on the research findings, it can be concluded that the use of adhesive as a precast concrete connector device should be carried out at the concrete age of 28 days with a thoroughly clean and dry surface of the connected concrete.